Kompetensi dan Etika Moral Pendidik Perspektif Al-Qur’an (Analisis Tafsir Tematik) - Abdul Muhaimin; Mas’ulil Munawaroh (Universitas Yudharta Pasuruan, 2021)
What is very important in education is how students have etiquette (moral ethics) in applying the knowledge they have gained, so that students deserve the title of Ulul Albab, meaning that the purpose of education is none other than to improve the morals or morals of students so that they have morality. KH. Hasyim 'Asya'ri stated that if the success of students is closely related to their adab (moral ethics) when studying, then the success of an educator will undoubtedly depend on his moral ethics when teaching. Because the problem of education cannot be separated from the term Ulul Albab, the duties and competencies of educators' moral ethics, the problem that the author will seek answers to is how the correlation between Ulul Albab and educators is, what are the duties of educators and what competencies must be possessed by an educator. This study uses a science of interpretation approach with accentuative theory and uses thematic method (al-mawdu'iyyah). The results of this study are the correlation between Ulul Albab and educators is very close, the duties of an educator other than murabby and mu'allim, as well as references, mentors and instructor, moral mentor and mudarris.The competence of an educator is intelligent, deep knowledge (al-Raisikhun fi al-'ilm), broad religious knowledge, while moral ethics must have akhlaq karimah